Comparison between cerebral state index and bispectral index as measures of electroencephalographic effects of sevoflurane using combined sigmoidal Emax model - Han Dong Woo; Linares-Perdomo Olinto-Jose; Lee Jong Seok; Kim Jun Ho; Kern Steven E (Acta Pharmacologica Sinica, 2016)
Aim: The cerebral state index (CSI) was recently introduced as an electroencephalographic monitor for measuring the depth of anesthesia. We compared the performance of CSI to the bispectral index (BIS) as electroencephalographic measures of sevoflurane effect using two combined sigmoidal Emax models. Methods: Twenty adult patients scheduled for laparotomy were studied. After induction of general anesthesia, sevoflurane concentrations were progressively increased and then decreased over 70 min. An analysis of the BIS and CSI with the sevoflurane effect-site concentration was conducted using two combined sigmoidal Emax models. Results: The BIS and CSI decreased over the initial concentration range of sevoflurane and then reached a plateau in most patients. A further increase in sevoflurane concentration produced a secondary plateau in the pharmacodynamic response. The CSI was more strongly correlated with effect-site sevoflurane concentration (R2=0.95±0.04) than the BIS was (R2=0.87±0.07) (P